Structure of Corporate Governance in Oil and Gas Industry-Post Corporate Scandals Will Regulatory Reforms Prevent Future Scandals? - Adenrele, Adebayo Alexander (2009)
In the past two decades corporate governance traditionally had been an internal affair between the principal (shareholders) and the agent (Managers) with some boundaries set by the state laws. Some economists, led by Milton Friedman argued that the main objective of business is to earn maximum profit for the shareholders. Imbalance and shift in power has resulted in increasing strain in the relationship between the principal. This has resulted in numerous corporate scandals aross the globe. This has resulted inadequate corporate governance both in the international and national oil companies and increasingly an intense scrutiny and introduction of federal laws. Corporate governance being the rigorous supervision of the management of a company or organization is not a new development but has become a subject of discussion amongst numerous scholars and pratitioners. With reforms and regulations being mandated on corporations it thus has become imperative to adopt the right Corporate Governance structure that would ensure businesses are run competently with integrity and due regard for the interest of the relevant shareholders.